2019
DOI: 10.1111/1541-4337.12433
|View full text |Cite
|
Sign up to set email alerts
|

Furan and Methylfurans in Foods: An Update on Occurrence, Mitigation, and Risk Assessment

Abstract: The acceptance of many foods is related to traditional cooking practices, which create taste and texture and are important to digestibility, preservation, and the reduction of foodborne illnesses. A wide range of compounds are formed during the cooking of foods, a number of these have been shown to lead to adverse effects in classical toxicological models and are known as food processing contaminants (FPC). It is essential that the presence and effects of such compounds alone and in combination within the diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 93 publications
(154 reference statements)
2
47
0
Order By: Relevance
“…Previously, 3-methylfuran has been identified as a volatile generated from various fungal species and could potentially be a biomarker for mold [ 29 ]. Furans, especially 2- and 3-methylfuran, have been identified as oxidation products of PUFAs, such as linolenic acid, and thus have been identified as food contaminants [ 30 ]. It is also possible that oxidation of isoprene resulted in the formation of the 2- and/or 3-methylfuran chemical signals [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, 3-methylfuran has been identified as a volatile generated from various fungal species and could potentially be a biomarker for mold [ 29 ]. Furans, especially 2- and 3-methylfuran, have been identified as oxidation products of PUFAs, such as linolenic acid, and thus have been identified as food contaminants [ 30 ]. It is also possible that oxidation of isoprene resulted in the formation of the 2- and/or 3-methylfuran chemical signals [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in Europe, EFSA has characterised that grain and grain-based products are chief sources of furans in children, but not in adults. In adults, coffee is the main contributor of furans (82) . Mitigation strategies depend on the food product and include lowering the thermal load, adding antioxidants, that delay lipid oxidation (82) .…”
Section: The Role Of Processing For Safety In Cereal-based Food Productsmentioning
confidence: 99%
“…In adults, coffee is the main contributor of furans (82) . Mitigation strategies depend on the food product and include lowering the thermal load, adding antioxidants, that delay lipid oxidation (82) . However, specific mitigation strategies are still under investigation (82) .…”
Section: The Role Of Processing For Safety In Cereal-based Food Productsmentioning
confidence: 99%
“…Significant uncertainty is reported on the risk to health posed by the consumption of furan with foods (Kettlitz et al., 2019). Thus, new strategies should be developed to eliminate its presence in foods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, new strategies should be developed to eliminate its presence in foods. In addition, preventive measures should be considered to reduce its formation during food‐processing operations (Kettlitz et al., 2019). Researchers have reported that furan is rapidly accumulated during heat treatment of canned and jarred baby food products when compared to products heated in an open container due to the thermal load in sealed vessels (Frank et al., 2020).…”
Section: Introductionmentioning
confidence: 99%